2014
DOI: 10.1177/1362361313516549
|View full text |Cite
|
Sign up to set email alerts
|

Reading and math achievement profiles and longitudinal growth trajectories of children with an autism spectrum disorder

Abstract: This study examined the reading and math achievement profiles and longitudinal growth trajectories of a nationally representative sample of children ages 6 through 9 with an autism spectrum disorder. Four distinct achievement profiles were identified: higher-achieving (39%), hyperlexia (9%), hypercalculia (20%) and lower-achieving (32%). Children with hypercalculia and lower-achieving profiles were more likely to be from low socioeconomic families and had lower functional cognitive skills than the higher-achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 27 publications
(35 reference statements)
4
71
1
5
Order By: Relevance
“…This subgroup has been frequently reported in prior studies of reading with individuals with ASD (e.g., Brown et al 2013;Jones et al 2009;Nation et al 2006;Newman et al 2007;Huemer and Mann 2010;Wei et al 2015;Zuccarello et al 2015) and shares characteristics with a language subgroup reported by Rapin et al (2009) whose members demonstrated adequate phonology and vocabulary alongside linguistic comprehension deficits. Grigorenko et al (2003) noted disagreement in the literature as to whether hyperlexia is synonymous with a reading comprehension disorder, or whether it is a unique condition characterized by an almost obsessive interest in letters and words, precocious and unprompted emergence of word decoding, and an extreme degree of discrepancy between word recognition and other cognitive skills that emerges between 3 and 5 years of age (Healy 1982).…”
Section: Hfasd Reading Subgroupssupporting
confidence: 61%
See 1 more Smart Citation
“…This subgroup has been frequently reported in prior studies of reading with individuals with ASD (e.g., Brown et al 2013;Jones et al 2009;Nation et al 2006;Newman et al 2007;Huemer and Mann 2010;Wei et al 2015;Zuccarello et al 2015) and shares characteristics with a language subgroup reported by Rapin et al (2009) whose members demonstrated adequate phonology and vocabulary alongside linguistic comprehension deficits. Grigorenko et al (2003) noted disagreement in the literature as to whether hyperlexia is synonymous with a reading comprehension disorder, or whether it is a unique condition characterized by an almost obsessive interest in letters and words, precocious and unprompted emergence of word decoding, and an extreme degree of discrepancy between word recognition and other cognitive skills that emerges between 3 and 5 years of age (Healy 1982).…”
Section: Hfasd Reading Subgroupssupporting
confidence: 61%
“…Similar to the subtypes described by Catts et al (2003) with a typically developing reading sample, many samples with ASD have displayed profiles comparable to poor comprehenders, or hyperlexics, who demonstrate adequate word decoding alongside poor language and reading comprehension (e.g. Brown et al 2013;Jones et al 2009;Nation et al 2006;Newman et al 2007;Huemer and Mann 2010;Wei et al 2015;Zuccarello et al 2015).…”
mentioning
confidence: 83%
“…For example, Wei et al (2014) examined the mathematics achievement profile of a nationally representative sample of children with ASD ages 6 through 9 using the Special Education Elementary Longitudinal Study (SEELS) data and found that these children had below average mathematics word problem solving and calculation abilities. These children's calculation ability was higher than their word problem solving ability.…”
Section: Mathematical Abilities Of Children With Asdmentioning
confidence: 99%
“…Mathematics represents one of a handful of skills routinely reported as a savant talent in autism, and indeed some individuals with ASD have shown extraordinary powers of calculation and mathematical reasoning (Howlin et al 2009; Treffert 2009). Beyond such rare cases, mathematics has been documented as an area of relatively spared or even enhanced performance in a large proportion of individuals with ASD (Chiang and Lin 2007; Iuculano et al 2014; Jones et al 2009; Wei et al 2015). …”
Section: Introductionmentioning
confidence: 99%